Pengaruh Senam Tai Chi terhadap Nyeri Lutut Lansia dengan Osteoarthritis (OA) dalam Perspektif Keperawatan Komunitas - M. Iqbal Sutisna; M. Naufal Abdullah; Siti Sepa Julianti; Adinda Siska Feronika; Diki Mubarok; Gina Maryati; Nita Amelia (Jurnal Kesehatan Amanah, 2026)
Knee osteoarthritis (OA) is a degenerative joint disorder frequently affecting older adults, characterized by symptoms such as pain, stiffness, and reduced physical capability. These symptoms can lead to decreased independence and a lower quality of life among the elderly. Tai Chi exercise is recognized as one of the recommended non-pharmacological approaches for managing osteoarthritis. This paper aims to explore the effects of Tai Chi exercise on alleviating knee pain in older adults with osteoarthritis. The methods applied include a literature review, a Pre-test Post-test design, and theoretical nursing care analysis using a community nursing framework. Pain intensity was measured using the Numeric Rating Scale (NRS). The Tai Chi program was conducted three times per week, with each session lasting 20–30 minutes. Findings show that Tai Chi exercise helps reduce knee pain intensity, enhances joint range of motion, strengthens muscles, and improves balance and physical mobility in the elderly. Furthermore, Tai Chi promotes relaxation, which aids in pain management by decreasing stress responses and increasing endorphin release. Overall, the study concludes that Tai Chi exercise is an effective non-pharmacological nursing intervention for managing knee pain in older adults with osteoarthritis and holds potential for incorporation into elderly healthcare programs.